Predicting the Future: Parental Progeny Investment in Response to Environmental Stress Cues - Gulyas, Leah; Powell, Jennifer R. (Frontiers in Cell and Developmental Biology, 2019)
Environmental stressors can severely limit the ability of an organism to reproduce as lifespan is decreased and resources are shifted away from reproduction to survival. Although this is often detrimental to the organism’s reproductive fitness, certain other reproductive stress responses may mitigate this effect by increasing the likelihood of progeny survival in the F1 and subsequent generations. Here we review three means by which these progeny may be conferred a competitive edge as a result of stress encountered in the parental generation: heritable epigenetic modifications to nucleotides and histones, simple maternal investments of cytosolic components, and the partially overlapping phenomenon of terminal investment, which can entail extreme parental investment strategies in either cytosolic components or gamete production. We examine instances of these categories and their ability to subsequently impact offspring fitness and reproduction. Ultimately, without impacting nucleotide sequence, these more labile alterations may shape development, evolution, ecology and even human health, necessitating further understanding and research into the specific mechanisms by which environmental stressors are sensed and elicit a corresponding response in the parental germline.